Characterizing the natural history of visual function in choroideremia using microperimetry and multimodal retinal imaging - Jolly, J; Xue, K; Edwards, T; Groppe, M; MacLaren, R (Association for Research in Vision and Ophthalmology, 2017)
PURPOSE. Centripetal retinal degeneration in choroideremia (CHM) leads to early visual field restriction and late central vision loss. The latter marks an acute decline in quality of life but visual prognostication remains challenging. We investigated visual function in CHM by correlating best-corrected visual acuity (BCVA), microperimetry and multimodal imaging. ?1 METHODS. Fifty-six consecutive CHM patients attending Oxford Eye Hospital were examined with BCVA, 10–2 microperimetry, optical coherence tomography, and fundus autofluorescence (AF). Microperimetry was repeated in 21 eyes and analyzed with Bland-Altman. KaplanMeier survival plots of eyes retaining 20/20 BCVA were created. Intereye symmetry was assessed. RESULTS. Microperimetry coefficient of repeatability was 1.45 dB. Survival analysis showed an indistinguishable pattern between eyes (median survival 39 years). Macular sensitivity showed a similar decline in right and left eyes, with half-lives of 13.6 years. Zonal analysis showed faster decline nasal to the fovea. Intereye symmetry was more consistent for microperimetry sensitivity (r ¼ 0.95, P < 0.001) than BCVA (r ¼ 0.42, P ¼ 0.0006). Near normal foveal sensitivity was maintained when the fovea was at least 2500 lm from the advancing edge of AF. CONCLUSIONS. BCVA is a marker of central degeneration and can provide valuable information about the position of the remaining retina as well as a measure of the impact on daily living. Microperimetry represents the global macular region. Both visual functions showed a high degree of intereye symmetry, particularly in early stages, indicating the fellow eye can provide a suitable control for assessing interventions to one eye. The findings may help to tailor visual prognosis and interpret outcomes of trials